An assessment of the onset of summer rainy season in Southern Africa - case study of Botswana - Cheruiyot, Denis C. (Department of Philosophy, 2023)
The economies of most Sub-Saharan African countries are linked to the onset, reliability and performance of seasonal rainfall. Failure of seasonal rains may signal food deficits or worse. Farmers, water conservationists and government bodies responsible for food security, all have an interest in seasonal rainfall: onset, approximate dates for start of the season and probabilities for early, normal or late onset of rains. This knowledge enables them make crucial decisions as to the choice of crops, planting dates, management of dams, pasture and hydro-electric dams. In this thesis, daily rainfall data for 29 rainfall stations in Botswana for the years 1971 - 2004 was analyzed to determine Start-of-Season (505)/ Onset of summer rainfall. We used Principal Component Analysis to determine rainfall homogeneous zones in Botswana. Basically three regions were identified for October, November December (OND) rainfall months. Rainfall values in representative stations in each zone (Northern, Central and South-Eastern and Western regions) were correlated with Sea Surface Temperatures (SSTs) in global oceans to determine ocean regions that correlate well with Botswana rainfall. The onset dates were grouped into false, early, normal, late and failed onsets. Monthly rainfall and Rainfall Onsets for selected 14 rainfall stations and ten other weather parameters, (that include SSTs, Sea Level Pressures (SLPs) and climate indices) were placed in a spreadsheet. Emergent Situation Awareness (ESA) for dynamic Bayesian networks (DBN) was used to analyze this data. The ESA for DBN models temporal dependencies among the weather parameters and climate indices using Direct Acyclic Graphs (DAG). This innovative DBN technology, ESA, reveals more detailed information from complex models. It reveals what is currently happening over time in a domain of interest. Each of the parameters and climate indices revealed varying degrees of beliefs for early, normal, late or failed rainfall onsets in Botswana. Some of the parameters which showed higher degrees of beliefs are promising signals to the onset of summer rains.